Lack of Self-Esteem in the Academic Performance of Grade 12 HUMSS Senior High Student at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focuses on the Lack of Self-esteem in the Academic Performance of Grade 12HUMSS Senior High Students at Bestlink College of the Philippines. According to SamuelFairlamb (2022), Self-Esteem has a lengthy history in connection to its relationship withsuccess and well-being, both of which are significant challenges in higher education. Thepresent paper examines how self-esteem, particularly when it is dependent and based onone’s academic performance, may be more harmful than helpful to these outcomes.The results from the data gathered show that Grade 12 HUMSS has influenced the overallcharacteristics of the students. These are all essential characteristics for the students as theirdriving force to engage themselves in the learning process. Furthermore, the data presentsthat the learning process is appealing not only to the cognitive domains but also to theaffective domains of the students.The researchers find the need to address the posited problem of the Lack of Self-Esteem inthe Academic Performance of Grade 12 HUMSS Senior High Students at Bestlink College ofthe Philippines. The study will focus on the development of all the aspects of the learner andthe need to improve the learning process.
Keywords: Development Studies